Djibouti opens its door to Kenyan dairy goats - Njagi, Stephen Mukundi (Technical Centre for Agricultural and Rural Cooperation, 2018)
A pilot project, which has imported 45 improved dairy goats from Kenya to Djibouti, is providing new and lucrative markets to small-scale goat breeders in Kenya. The project partners are also assessing the performance of the adaptability of the Kenyan goats to Djibouti by monitoring their health, milk production, breeding and feeding.